KEDUDUKAN WALI NANGGROE DI ACEH - Baihaqi A Samad (SCAD Independent, 2014)
Law on Governing Aceh instructs is Wali Nanggroe an institution for the benefit of the people and the future of governance in Aceh. as the 'Wali' in point 1.1.7 of the Helsinki MoU and Law. No. 11/2006, must be traced to its roots in the context of the Imamate, socio-political, legal and moral. The person who bears the title